Investigation by Raman Spectroscopy of the Decomposition Process of HKUST-1 upon Exposure to Air - Michela Todaro; Antonino Alessi; Luisa Sciortino; Simonpietro Agnello; Marco Cannas; Franco Mario Gelardi; Gianpiero Buscarino (Journal of Spectroscopy)
We report an experimental investigation by Raman spectroscopy of the decomposition process of Metal-Organic Framework (MOF) HKUST-1 upon exposure to air moisture (T=300 K, 70% relative humidity). The data collected here are compared with the indications obtained from a model of the process of decomposition of this material proposed in literature. In agreement with that model, the reported Raman measurements indicate that for exposure times longer than 20 days relevant irreversible processes take place, which are related to the occurrence of the hydrolysis of Cu-O bonds. These processes induce small but detectable variations of the peak positions and intensities of the main Raman bands of the material, which can be related to Cu-Cu, Cu-O, and O-C-O stretching modes. The critical analyses of these changes have permitted us to obtain a more detailed description of the process of decomposition taking place in HKUST-1 upon interaction with moisture. Furthermore, the reported Raman data give further strong support to the recently proposed model of decomposition of HKUST-1, contributing significantly to the development of a complete picture of the properties of this considerable deleterious effect.